Increased D‐serine in the aqueous and vitreous humour in patients with proliferative diabetic retinopathy. (8th May 2014) - Jiang, Haiyan; Du, Jinlin; He, Tao; Qu, Jia; Song, Zongming; Wu, Shengzhou
Abstract Background The objective of this clinical study is to examine the association between D‐serine and diabetic retinopathy (DR). Design Retrospective, case‐control study was performed in the affiliated Eye Hospital of Wenzhou Medical University. Participants This study included 25 patients with proliferative diabetic retinopathy (PDR), and 25 sex‐ and age‐matched control subjects, i.e. patients with idiopathic macular hole and idiopathic epiretinal membrane. Methods Clinical diagnoses were made by the senior ophthalmologists in the Eye Hospital; the aqueous and vitreous humour specimens were collected from these patients undergoing pars plana vitrectomy for treating complications. Main Outcome Measures The aqueous and vitreous levels of D‐serine and glutamate were measured with reverse‐phase high‐performance liquid chromatography (HPLC); the contents of haemoglobin in the blood and in the vitreous specimens from PDR were measured with spectrophotometry to correct possible introduction of amino acids from PDR haemorrhage. Results The concentrations of D‐serine in the aqueous or vitreous humour were significantly higher in patients with PDR compared with control subjects. The vitreous concentrations of D‐serine in PDR were 25.55 ± 0.63 μmol/L compared with control subjects at 22.76 ± 0.36 μmol/L (P = 0.002); the levels of D‐serine in the aqueous humour from patients with PDR were 29.08 ± 1.31 μmol/L compared with control subjects at 24.22 ± 0.65 μmol/L (P = 0.006). Correction from possible introduction of D‐serine from the vitreous haemorrhage in PDR did not significantly alter the findings. Conclusions Increased D‐serine in the aqueous and vitreous humour was found in patients with PDR compared with control subjects.